Influences of Etomidate Combined with Propofol on Cognitive Function, Inflammation and Immunity in Patients Undergoing Gastric Cancer Surgery: Etomidate and Propofol on Gastric Cancer Surgery - Tian, Xiuwen (Cellular and Molecular Biology, 2023)
This study examined how etomidate combined with propofol affected cognitive function, inflammation, and immunity in patients undergoing gastric cancer surgery. 182 gastric cancer patients treated in our hospital were enrolled and randomly divided into two groups, namely group A (anesthetized using etomidate) and group B (anesthetized using etomidate combined with propofol). Then the cognitive function, inflammation and immunity indicators were determined in the two groups. Compared with group A, group B exhibited shorter operation duration and hospital stay and smaller bleeding volume (p<0.01). At 3 d after the operation, group B had a higher Ramsay score, but a lower visual analogue scale (VAS) score than group A (p<0.05). Moreover, the mini-mental state examination (MMSE) score was lower in group A than that in group B (p<0.01). At the end of the operation, the heart rate (HR), mean arterial pressure (MAP) and saturation of pulse oxygen (SpO2) were decreased to a great extent in both groups compared with those before anesthesia (p<0.05). Compared with those before anesthesia, the levels of immunoglobulin (Ig)M, IgG and IgA were lower in group A at the end of the operation and 1 and 3 d after the operation (p<0.05), but they were substantially higher in group B than those in group A (p<0.05). At the end of the operation and 1 and 3 d after the operation, the levels of the T-cell subset indicators decreases in group A were greater than those in group B (p<0.05). Etomidate combined with propofol has few influences on the immune and cognitive functions of gastric cancer patients and can effectively lower the expression levels of inflammatory factors in these patients.